Effect of Blended Approach on the Academic Achievement of Low Achievers in the Subject of Education at Higher Secondary Level: Raheela Anjum, Rehmat Ali Farooq,Rabia Tabassum (PJDOL, 2023)
The purpose of the study was to inquire the effects of blended approach on the academic achievements of low achievers in the Education subject at higher secondary level. For this study, pretest and the posttest equivalent group experimental research was carried out for data collection. All the students studying in 11th class in Federal Government Model Colleges of Islamabad served as population of current study. Accessible population of the study were all students studying in 11th class in selected college for experiment. Thirty students of 1 st year class were sample of study and then on basis of pre-test performance, they were equated and distributed into two groups. Each group comprised of fifteen students. Teacher made pretest and posttest was developed. Experiment was provided to both of groups. For pre-test grades, post-test and retention test were examined at 0.05 level of significance by using t-test through SPSS. It was concluded that blended approach was much better as compared to conventional methodology in the academic achievement ofstudents on posttest and even on retention test. It was recommended that blended approach should be used at college level for teaching-learning process.